Copper Containing SBA-15 Prepared Through pH Modification Methods and its Catalytic Activity for N2O Decomposition - Mohd Ridzuan, Nordin; Mohd Husin, Mohd Haizal; Li, Jinlin; Liew, Kong Yong; Chin, S. Y. (SCUN, 2012)
Copper-substituted SBA-15 (Cu/SBA-15) mesoporous materials were directly synthesized under acidic conditions by a pH modification method using hexamethylenetetramine (HMTA) as an internal pH-modifier. The synthesized material has been characterised by XRD, SEM-EDX, TEM and FTIR. The results showed that the resultant materials exhibit highly ordered hexagonal mesoporous structures. In addition, the HMTA also strongly affected the incorporation of copper in the silica framework. During hydrothermal process the HMTA dissociates to release NH3 and increases the internal pH value and helps to introduce more copper into SBA-15 framework. Catalytic screenings reveal that Cu/SBA-15 materials can be used as potential catalyst for the decomposition of N2O. The Cu/SBA-15 (1:10) have good catalytic activity causing 50% of N2O to decomposed at 600oC.